Modifying Chromatin by Histone Tail Clipping. Issue 18 (14th September 2018) - Azad, Gajendra Kumar; Swagatika, Swati; Kumawat, Manoj; Kumawat, Ramesh; Tomar, Raghuvir Singh
Abstract: Post-translational modifications (PTMs) of histone proteins play a crucial role in the regulation of chromatin structure and functions. Studies in the last few decades have revealed the significance of histone PTMs in key cellular processes including DNA replication, repair, transcription, apoptosis and cell cycle regulation. The PTMs on histones are carried out by chromatin modifiers, which are reversible in nature. The dynamic activity of chromatin modifiers maintains the levels of different PTMs on histones. The modified histones are recognized by reader proteins, which recruit effector proteins to regulate the function. The interplay between histone PTMs and chromatin dynamics plays a major role in the regulation of most of the cellular processes. Importantly, the perturbations in the histone PTMs by various intrinsic or extrinsic factors can cause defects in fundamental cellular processes leading to a wide range of diseases. The proteolytic clipping of histone proteins has also been shown to regulate many biological processes. Histone clipping has been observed from yeast to mammals, suggesting that this mechanism is a conserved epigenetic phenomenon. In this review, we have summarized the significance of histone clipping and provided future directions to comprehend the mechanism of this distinct and poorly understood epigenetic event. Graphical Abstract: Unlabelled Image Highlights: The proteolytic clipping of histone proteins seems to regulate many biological functions. The clipping of histone H3 has been found to regulate differentiation of stem cells in mouse and expression of sporulation phase-specific genes in yeast. The clipping of histone H3 has also been observed in the liver of chicken and correlates with the aging process. Clipping of histones have been found during cancer and human individuals exposed to arsenic. Complete understanding about the role of histone clipping under various pathophysiological conditions is not clear.